Thermal degradation behaviour of two methacrylate polymers with side chain amide groups - Coskun, M; Erol, I; Coskun, MF; Demirelli, K (Elsevier Sci Ltd, 2002)
2-Oxo-2-phenylamino)ethylene methacrylate (PAMA) and (2-oxo-2-benzylamino)ethylene methacrylate (BAMA) were prepared by reaction of sodium methacrylate with N-phenyl chloroacetamide and N-benzyl chloroacetamide, respectively, which were obtained from reaction of chloroacetyl chloride with aniline or benzylamine. The thermal degradations of poly(PAMA) and poly(BAMA) prepared by a free-radical procedure were investigated by thermogravimetric analysis (TG) and by programmed heating of the polymer from ambient temperature to 500 degreesC under vacuum, followed by product collection, and using IR spectra of partially degraded polymer. The products volatile at degradation temperature but not at ambient temperature were collected on the cooled upper part of the degradation tube [cold ring fraction, CRFP for poly(PAMA), CRFB for poly(BAMA)]. Product analysis studies showed that only N-benzyl hydroxyacetamide formed as major product in thermal degradation of poly(BAMA) and the monomer did not, whereas in the case of poly(PAMA) N-phenyl hydroxyacetamide and the monomer both formed as major products. For poly(BAMA), the activation energy of cyclization is calculated as 47.4 kJ mol(-1); for poly(PAMA) the activation energy of the depolymerization is calculated as 58 kJ mol(-1). The mechanism of thermal degradation including formation of the major products is discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: methacrylate; amide side chain; thermal degradation